In Vitro Transcription of Simian Virus 40 Sequences in SV3T3 Chromatin - Astrin, Susan M. (1973)
The template properties of chromatin were studied in a system in which transcription of unique genes could be examined. Chromation and DNA were isolated from SV3T3 cells, a line of simian virus 40 (SV40)-transformed mouse cells, and used as templates for Escherichia coli RNA polymerase. The SV40 sequences in the RNA transcribed in vitro and in RNA isolated from the transformed cells were analyzed by hybridization to radioactive RNA transcribed from SV40 DNA. The results indicate that the same sequences of the SV40 “-” strand (DNA strand which serves as a template for early RNA) are transcribed in vitro from chromatin as are found in transformed cells. In contrast, when the DNA isolated from SV3T3 chromatin by removal of proteins is used as a template, the entire SV40 “-” strand is transcribed. It is concluded that the specific template restriction observed with chromatin is due to the presence of proteins associated with the DNA.